The other Russia. Local experience and societal change - Granberg, L.; Saetre, A.-M. (Studies in contemporary Russia, 2017)
`We belong to the generation that doesn`t have the habit of taking money.` (A woman from a women`s club, forest village)This is a book about Russia on the local level, about its people, their concerns and actions, about how to survive from day to day or how to attempt to make life better in the future. The text is based on interviews which the writers collected during numerous visits to Russian regions between 2001 and 2015. Interviews were conducted in five regions: some places were visited many times and even followed for the whole period, while others were visited only once or twice. We did not choose these regions just for this book, they were targets of several sepa-rate projects with specific aims, and their results have been reported elsewhere. All of these projects, however, paid attention to the local level, and for all of them the data was collected by interviewing people, complemented by observing and in some cases by special methods like focus group meetings.